Hyperspherical analysis of radial correlations in four-electron atoms - Morishita, Toru; Lin, C. D. (My University, 2005)
Hyperspherical coordinates are used to study electron correlations in the radial motion of a four-electron atom within the model of s4 configurations. We identify groups of hyperspherical adiabatic potential curves that support singly, doubly, triply, and quadruply excited states. By examining the nodal structures of the channel functions, we show that it is possible to relate the number of nodal surfaces in the hyperangles and the principal quantum numbers used in the independent particle picture.